Amazing But Quite Confusing Series

Calculus Level 4

1 + 2 3 1 ! + 3 3 2 ! + 4 3 3 ! + \large 1 + \frac{2^{3}}{1!} + \frac{3^{3}}{2!} + \frac{4^{3}}{3!} + \cdots

Find the value of the closed form of the above series to 3 decimal places.


Notation: ! ! is the factorial notation. For example, 8 ! = 1 × 2 × 3 × × 8 8! = 1\times2\times3\times\cdots\times8 .


The answer is 40.774.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Chew-Seong Cheong
Apr 15, 2017

Similar solution with Dhanvanth Balakrishnan 's

Let S = 1 + 2 3 1 ! + 3 3 2 ! + 4 3 3 ! + = n = 0 ( n + 1 ) 3 n ! \displaystyle S=1+\frac {2^3}{1!} +\frac {3^3}{2!} +\frac {4^3}{3!}+\dots = \sum_{n=0}^\infty \frac {(n+1)^3}{n!} . Consider the following:

n = 0 x n n ! = e x Multiply both sides by x n = 0 x n + 1 n ! = x e x Differentiate both sides w.r.t. x n = 0 ( n + 1 ) x n n ! = e x + x e x Multiply both sides by x n = 0 ( n + 1 ) x n + 1 n ! = x e x + x 2 e x Differentiate both sides w.r.t. x n = 0 ( n + 1 ) 2 x n n ! = e x + 3 x e x + x 2 e x Multiply both sides by x n = 0 ( n + 1 ) 2 x n + 1 n ! = x e x + 3 x 2 e x + x 3 e x Differentiate both sides w.r.t. x n = 0 ( n + 1 ) 3 x n n ! = e x + 6 x e x + 7 x 2 e x + x 3 e x Put x = 1 n = 0 ( n + 1 ) 3 n ! = 15 e 40.774 \begin{aligned} \sum_{n=0}^\infty \frac {x^n}{n!} & = e^x & \small \color{#3D99F6} \text{Multiply both sides by }x \\ \sum_{n=0}^\infty \frac {x^{n+1}}{n!} & = xe^x & \small \color{#3D99F6} \text{Differentiate both sides w.r.t. }x \\ \sum_{n=0}^\infty \frac {(n+1)x^{n}}{n!} & = e^x + xe^x & \small \color{#3D99F6} \text{Multiply both sides by }x \\ \sum_{n=0}^\infty \frac {(n+1)x^{n+1}}{n!} & = xe^x + x^2e^x & \small \color{#3D99F6} \text{Differentiate both sides w.r.t. }x \\ \sum_{n=0}^\infty \frac {(n+1)^2x^{n}}{n!} & = e^x + 3xe^x + x^2e^x & \small \color{#3D99F6} \text{Multiply both sides by }x \\ \sum_{n=0}^\infty \frac {(n+1)^2x^{n+1}}{n!} & = xe^x + 3x^2e^x + x^3e^x & \small \color{#3D99F6} \text{Differentiate both sides w.r.t. }x \\ \sum_{n=0}^\infty \frac {(n+1)^3x^{n}}{n!} & = e^x + 6xe^x + 7x^2e^x + x^3e^x & \small \color{#3D99F6} \text{Put }x=1 \\ \sum_{n=0}^\infty \frac {(n+1)^3}{n!} & = 15e \approx \boxed{40.774} \end{aligned}

We know that the expansion of exponential function is,

e x \large e^{x} = 1 \large 1 + \large + x \large x + \large + x 2 2 ! \large \frac{x^{2}}{2!} + \large + x 3 3 ! \large \frac{x^{3}}{3!} + \large + x 4 4 ! \large \frac{x^{4}}{4!} + \large + . . . \large ...

By multiplying x \large x on both sides,

x e x \large xe^{x} = x \large x + \large + x 2 \large x^{2} + \large + x 3 2 ! \large \frac{x^{3}}{2!} + \large + x 4 3 ! \large \frac{x^{4}}{3!} + \large + x 5 4 ! \large \frac{x^{5}}{4!} + \large + . . . \large ...

Differentiating w.r.t x \large x on both sides,

x e x + e x \large xe^{x}+e^{x} = 1 \large 1 + \large + 2 x \large 2x + \large + 3 x 2 2 ! \large \frac{3x^{2}}{2!} + \large + 4 x 3 3 ! \large \frac{4x^{3}}{3!} + \large + 5 x 4 4 ! \large \frac{5x^{4}}{4!} + \large + . . . \large ...

So by repeating this process 2 \large 2 times, we get,

7 e x \large 7e^{x} + \large + 6 x 2 e x \large 6x^{2}e^{x} + \large + e x \large e^{x} + \large + x 3 e x \large x^{3}e^{x} = \large = 1 \large 1 + \large + 2 3 x \large 2^{3}x + \large + 3 3 x 2 2 ! \large \frac{3^{3}x^{2}}{2!} + \large + 4 3 x 3 3 ! \large \frac{4^{3}x^{3}}{3!} + \large + 5 3 x 4 4 ! \large \frac{5^{3}x^{4}}{4!} + \large + . . . \large ...

By substituting x \large x = \large = 1 \large 1 ,

1 \large 1 + \large + 2 3 1 ! \large \frac{2^{3}}{1!} + \large + 3 3 2 ! \large \frac{3^{3}}{2!} + \large + 4 3 3 ! \large \frac{4^{3}}{3!} + \large + . . . \large ... = \large = 15 e \large 15e = \large = 40.774 \large 40.774

Anirban Karan
Apr 16, 2017

I = 1 + 2 3 1 ! + 3 3 2 ! + 4 3 3 ! + . . . . . . = n = 0 ( n + 1 ) 3 n ! \displaystyle I=1+\frac {2^3}{1!} +\frac {3^3}{2!} +\frac {4^3}{3!} +......= \sum_{n=0}^\infty \frac {(n+1)^3}{n!}

Now, let ( n + 1 ) 3 = a [ n ( n 1 ) ( n 2 ) ] + b [ n ( n 1 ) ] + c n + d (n+1)^3=a [n(n-1)(n-2)]+b [n(n-1)]+c n+d

n 3 + 3 n 2 + 3 n + 1 = a n 3 + ( b 3 a ) n 2 + ( 2 a b + c ) n + d \implies n^3+3 n^2+3 n+1= a n^3+(b-3 a) n^2+(2 a-b+c)n+d

From this identity, one can easily get, a = 1 , b = 6 , c = 7 , d = 1 a=1, b=6, c=7, d=1 .

Then, I = 1 + 2 3 1 ! + 3 3 2 ! + n = 3 ( n + 1 ) 3 n ! = 1 + 2 3 1 ! + 3 3 2 ! + n = 3 [ a ( n 3 ) ! + b ( n 2 ) ! + c ( n 1 ) ! + d n ! ] = 1 + 2 3 1 ! + 3 3 2 ! + a m = 0 1 m ! + b ( m = 0 1 m ! 1 ) + c ( m = 0 1 m ! 1 1 ) + d ( m = 0 1 m ! 1 1 1 2 ! ) = ( 9 b 2 c 2 d + 27 d 2 ) + ( a + b + c + d ) e [ as e = m = 0 1 m ! ] \begin{aligned} I&=1+\frac {2^3}{1!} +\frac {3^3}{2!}+\sum_{n=3}^\infty \frac {(n+1)^3}{n!}&\\ &=1+\frac {2^3}{1!} +\frac {3^3}{2!}+\sum_{n=3}^\infty \Big[\frac {a}{(n-3)!}+\frac {b}{(n-2)!}+\frac {c}{(n-1)!}+\frac {d}{n!}\Big]&\\ &=1+\frac {2^3}{1!} +\frac {3^3}{2!}+a\sum_{m=0}^\infty \frac {1}{m!}+b\Big(\sum_{m=0}^\infty \frac {1}{m!}-1\Big)+c\Big(\sum_{m=0}^\infty \frac {1}{m!}-1-1\Big)+d\Big(\sum_{m=0}^\infty \frac {1}{m!}-1-1-\frac{1}{2!}\Big)&\\ &=\Big(9-b-2c-2d+\frac{27-d}{2}\Big)+(a+b+c+d)e\quad\small \color{#3D99F6} \Big[\text{as } e=\sum_{m=0}^\infty \frac {1}{m!}\Big]&\\ \end{aligned}

Now, putting the values of a , b , c , d a,b,c,d we get, I = 15 e = 40.774 \boxed{I=15e=40.774}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...